Real-life measurement of size-fractionated aerosol concentration in a plethysmography box during the COVID-19 pandemic and estimation of the associated viral load. (December 2021) - Tomisa, G.; Horváth, A.; Farkas, Á.; Nagy, A.; Kis, E.; Tamási, L.
Summary: Introduction: There are concerns about pulmonary function tests (PFTs) being associated with aerosol generation and enhanced virus transmission. As a consequence, the number of PFTs was reduced significantly during the coronavirus disease 2019 pandemic. However, there are no robust data supporting this fear. Objectives: To perform real-life measurement of aerosol concentrations in a PFT laboratory to monitor the concentration of particles near the patient, and to model the associated potential viral load. Methods: Two optical particle counters were used to sample the background concentration and the concentration of particles near the patient's mouth in a whole-body plethysmography box. Statistical evaluation of the measured particle concentration time series was completed. The particle exhalation rate was assessed based on the measured particle concentration data by applying the near-field/far-field theory. The number of exhaled viruses by an infected patient during the test was compared with the emission of viruses during quiet breathing and speaking. Results: Twenty-five patients were included in the study. Eighteen patients showed a significant increase in aerosol concentration [mean 1910 (standard deviation 593) particles/L]. Submicron particles dominated the number size distribution of the generated particles, but large particles represented a higher volume fraction in the generated particles compared with background. An average gene exhalation rate of 0.2/min was estimated from this data. This is one order of magnitude higher than the release rate for the same infected person during quiet breathing, and of the same order of magnitude as the release rate during normal speaking. Conclusions: This study demonstrated that PFTs are aerosol-generating procedures. Based on these results, the moderate increase in viral load does not underpin stopping such examinations.